Supervisi Pembelajaran Kitab di Pondok Pesantren Al-Istiqomah Tanjungsari Petanahan - Kebumen - Dzokar, Dudayyev; Sukataman, Sukataman (LPPM IAINU Kebumen, 2023)
This research discusses the implementation of supervision at the Al-Istiqomah Tanjungsari Petanahan Kebumen Islamic Boarding School and determines the obstacles and solutions faced in implementing supervision at the Al-Istiqomah Tanjungsari Petanahan Islamic Boarding School, Kebumen. This research is a qualitative research type of field research, where the author collects data by conducting in-depth studies in the form of interviews with caregivers, caregiver councils, ustadz/ustadzah, as interview subjects observing the phenomena that occur and documenting the data. Then the data was analyzed using qualitative descriptive methods which were intended to describe factual situations. The collected data was analyzed using data reduction, data presentation, and drawing conclusions. The results of research on the implementation of supervision at the Al-Istiqomah Islamic Boarding School, Tanjungsari Petanahan, Kebumen, show that the implementation of supervision at the Al-Istiqomah Islamic Boarding School, Tanjungsari, Petanahan, Kebumen is quite good, where in implementing this supervision, a kyai as a supervisor really helps improve the teaching abilities of the ustadz/ustadzah in the process. learning so that the book learning system at the al-istiqomah Islamic boarding school runs effectively in accordance with the vision and mission.